Desain Didaktis Pada Pelajaran al-Qur’an Hadist berdasarkan Analisis Hypothetical Learning Trajectory (HTL) terhadap Learning Obstacle Siswa Kelas XI - Yusnimar Yusnimar (Lembaga Anotero Scientific Pekanbaru, 2022)
This study based on the results of teachers discussions with preliminary data in the form of students’ cognitive test results and class observations. Cognitive tests of students were carried out aiming to see the problems that students often faced in learning Al-Qur’an Hadith. Problem that arise include; 1) students have difficulty memorizing verses and hadith, 2) difficult to master the interpretation and interpretation of the arguments provided in learning, 3) and it is difficult to practice the law of reading (tajwid). This is because learning Al-Qur’an Hadith is theoretical in nature so it necessary to prepare a learning design that is able to facilitate students learning and understanding the concept of Al-Qur’an Hadith. The learning design is based on a hypothetical learning trajectory (HTL) analysis of students cognitive abilities. This research is a descriptive analysis with a participant of 30 students of class XI. The result of study provide information for further research in the development of a didactical design that is hypthesized to improve students understanding in learning the Al-Qur’an and Hadith